Python-Based Interactive Simulation in STEM E-LKPD to Increase Sustainability Awareness on Global Warming Material - Lita Luciana; Leni Marlina; Apit Fathurohman (Postgraduate, University of Mataram, 2025)
This study aims to present the design and efficacy of an enhanced learning tool for digital platforms featuring interactive simulations to educate students about the complexities of global warming. This study utilized an experimental method involving 32 10th-grade high school students. The Python-assisted E-Learning Tool offers dynamic visualization and model interaction, allowing students to explore the causal relationship between human activities and climate change. By manipulating simulation parameters, students observed the impact of global temperature trends in real-time, which fostered a nuanced understanding of global warming. This allows them to observe the cause-and-effect relationship between human activities, greenhouse gas emissions, and environmental impact. Interactive simulations and applications enable students to experiment independently with physics concepts. Python underscores its suitability for education because of its extensive functionality and ease of use and because it encourages a hands-on and exploratory approach to learning complex STEM subjects such as global warming. This process is accompanied by structured instructional content, including data analysis, group discussion, and reflective assessment, to enhance cognitive engagement and promote ongoing practice. This study highlights the potential of integrating technology-based learning tools into the STEM curriculum to facilitate active exploration of global sustainability challenges.